Transformational Leadership Caregiver In Caring To Hemodialysis Patient: Literature Review - Theodora Rosaria Geglorian; Sri Hidayati; Ani Ratnaningsih; Arifin Dwi Atmaja (MULTIPLE: Journal of Global and Multidisciplinary, 2024)
End stage chronic kidney disease ranks 16th as a cause of death according to the Global Burden of Disease data from 2017. Patients with end-stage chronic kidney disease experience various impacts, such as depression, fatigue, cramps, nausea, vomiting, and a range of other physical, psychological, and social disorders. As a result, patients are highly dependent on their families. However, under these conditions, families often feel afraid to touch and talk to the patient during hemodialysis. This causes stress in the family, which can affect the patient's condition, such as a decrease in coping mechanisms. To enhance the patient's coping mechanisms, families can apply transformational leadership. The goal of this literature review is to identify transformational leadership in the care of hemodialysis patients. This study utilized articles and books accessible through Ebsco, Pro Quest, Pubmed, Emerald Insight, and Science Direct, from 2008 to 2024. The keywords used were transformational leadership, nursing, family care, and coping in hemodialysis patients. The findings indicate that transformational leadership can create comfort between patients and their families, improve communication, reduce stress, and enhance coping mechanisms in hemodialysis patients. Additionally, emotional aspects can be improved with this type of leadership. In conclusion, transformational leadership can be applied in the care of hemodialysis patients and can enhance constructive coping in these patients, thereby reducing morbidity and mortality among hemodialysis patients.